ICASSP 2020 - 2020 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2020
DOI: 10.1109/icassp40776.2020.9053168
|View full text |Cite
|
Sign up to set email alerts
|

Formulating Divergence Framework for Multiclass Motor Imagery EEG Brain Computer Interface

Abstract: Similar to most of the real world data, the ubiquitous presence of non-stationarities in the EEG signals significantly perturb the feature distribution thus deteriorating the performance of Brain Computer Interface. In this letter, a novel method is proposed based on Joint Approximate Diagonalization (JAD) to optimize stationarity for multiclass motor imagery Brain Computer Interface (BCI) in an information theoretic framework. Specifically, in the proposed method, we estimate the subspace which optimizes the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Another common issue is the stationarity preservation of MI EEG data. We may take the gradient descent on an orthogonal manifold as a meaningful reference to enforce the stationarity of EEG [38][39], which could improve the accuracy. Also, there are some points we can improve even though we made the frequency band dependent model performance evaluation.…”
Section: Limitation and Prospectmentioning
confidence: 99%
“…Another common issue is the stationarity preservation of MI EEG data. We may take the gradient descent on an orthogonal manifold as a meaningful reference to enforce the stationarity of EEG [38][39], which could improve the accuracy. Also, there are some points we can improve even though we made the frequency band dependent model performance evaluation.…”
Section: Limitation and Prospectmentioning
confidence: 99%
“…Although various BCI algorithms have been examined, research on efficient feature extraction by considering the essence of EEG signals is still ongoing. According to Kumar et al [72], the almost constant presence of nonstationarities in EEG signals degrades BCI performance. In an information theoretic context, the authors suggested a novel strategy based on Joint Approximate Diagonalization (JAD) to optimize stationarity for multiclass motor imagery BCIs.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, BCI has significant applications in various fields such as automobiles, robotics and is widely used in medical treatment. 3 To monitor the brain activities, numerous techniques such as Electrocorticography (ECoG), functional magnetic resonance imaging (fMRI), magneto-encephalography (MEG), and electroencephalogram (EEG) are used. 4 Since EEG is non-invasive, portable, and low in cost, it is one of the widely used neuroimaging technology to record the brain activities.…”
Section: Introductionmentioning
confidence: 99%